UAV-Assisted NOMA-Based Network with Alamouti Space-Time Block Coding - Yilmaz, Tayfun; Ayranci, Ahmet Aytug; Bacanli, Emre; Ilhan, Haci (GAZI UNIV, 2022)
In this study, a 3-user system was considered in the Unmanned Aerial Vehicle-Assisted (UAV-Assisted) Non-Orthogonal Multiple Access-Based (NOMA-Based) communication network. In the network, UAV communicates with users on the ground via two antennas using the Alamouti Space-Time Block Coding (A-STBC) technique. It is considered that there are two separate scenarios where user links are designed with one antenna and two antenna systems. In the study, Monte-Carlo simulations were carried out to understand the effects of using the A-STBC technique in UAV-Assisted NOMA-Based communication networks and increased antenna diversity in receiver and transmitter in the network to the performance of the system. For the benchmark, the downlink NOMA network was used, where the receivers and the UAV are designed with a single antenna. In the simulation results, with the A-STBC technique in the system and increase in diversity, the effects of Path Loss (PL) and environmental factors on error performance were examined. Especially in high Signal to Noise Ratio (SNR) values, it has been observed that the effects of these destructive factors on error performance are highly minimized. Also, the use of A-STBC technique and the increase in diversity in the system provided considerable SNR gain. Moreover, it has been observed that full diversity gain can be achieved when the A-STBC technique is used in the UAV-Assisted downlink NOMA-Based communication system.
Keywords: Non-orthogonal multiple access; unmanned aerial vehicles; A-STBC; diversity; bit error rate; NONORTHOGONAL MULTIPLE-ACCESS; Engineering